Pathways to Green Jobs: An Analysis of the Opportunities and Obstacles in the Green Jobs Market for Boston's Chinese Community. - Crowe, Jonathan.; Levine, Rachel.; Sanchez, Juan. (Tufts University. Tisch Library., 2018)
2009 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Chinese Progressive Association.